Analisis Kausalitas dalam Pertanggungjawaban Pidana Korupsi Pasca Mutasi Jabatan: Studi Putusan Mahkamah Agung Nomor 8681 K/Pid.Sus/2025 - Muhamad Zainal Arifin; Bambang Wiyono; Muhammad Sa’dullah (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study examines criminal liability for corruption committed by public officials after job mutation, with particular attention to the application of causality theory in Supreme Court Decision Number 8681 K/Pid.Sus/2025. The legal issue arises from the temporal gap between administrative actions taken during the defendant’s tenure and the emergence of state losses after the official no longer held the relevant position. This situation raises questions regarding the limits of criminal responsibility and the existence of a legally relevant causal link. The research aims to analyze how the Supreme Court constructed criminal liability and applied causality theory in determining responsibility under such circumstances. Using a normative juridical method with statutory, case, and conceptual approaches, this study analyzes legislation, judicial decisions, and doctrinal theories on criminal liability and causation. The findings show that the defendant’s administrative recommendation, issued lawfully during his tenure, did not have a direct and adequate causal relationship with the unlawful land sale conducted by third parties several years later. The emergence of an intervening cause and the loss of control after job mutation indicate a break in the chain of causation. This study concludes that the application of causality theory in corruption cases must be proportional and consistent with the principles of tempus delicti, individual criminal responsibility, and legal certainty.